Life events and parasuicides in Hospital Kuala Lumpur, Malaysia - Awang, Hamidin; Thambu, Maniam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Objective: The aim of this study is to compare the prevalence of life events among parasuicide patients with the prevalence of similar life events among age, sex and race matched patients with non-chronic medical illness. Methods: A hospital-based case-control study using convenience sampling method was conducted in Hospital Kuala Lumpur for a period of three and a half months. A total of 50 patients admitted consecutively after an episode of parasuicide and who fulfilled criteria for entry into the study agreed to participate. For each case one age-, sex- and race-matched control was selected from the list of patients who were admitted to the same hospital for non-chronic medical illness. Result: Statistical analysis showed that compared with medically ill patients, parasuicide patients had significantly higher prevalence of threatening life events six months (p<0.001) before their act and these life events were significantly concentrated in the last one month before the attempt (p=0.001). Among the seven categories of life events, cases had a significant excess of interpersonal problems (p<0.001) that included serious problems with a close friend, neighbour or relative, break-up of a steady relationship and separation due to marital difficulties. Conclusion: The results suggest that there is a high prevalence of life events among parasuicide patients when compared with medically ill patients especially during the month prior to their admission to the hospital. The data also indicate that there is a significant association between suicide attempts and interpersonal problems.